VET teacher training : a comparison of university programs in the U.S. and Norway - Zirkle, Chris [Verfasser]; Smeplass, Eli [Verfasser]; Leraand, Arve [Verfasser] (My University, 2024)
“This article is a study of Vocational Education and Training (VET) teacher training in considerably different societal contexts. Vocational education teachers contribute to the growth and development of a country’s future workforce, as they bridge the gap between formal schooling and the workplace. Their training is critical, since their pedagogical knowledge and technical expertise can result in students prepared to enter their chosen field of employment. Through case studies analyzing qualitative data on 1) program entry requirements, 2) curricular and course components, 3) implementation of practical elements in the training and 4) definitions of formal qualifications, the researchers identify joint key elements in VET teacher training programs in the U.S. and Norway. The discussion highlights how quality VET teacher training programs play a pivotal role in bridging between the practical elements in vocational education and professional futures as teachers.” (authors’ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; S 1.4 Hochschulbildung; I 2.3.2 Nordamerika; I 2.2.1 Westeuropa; 370; Berufsschullehrer; Lehrerausbildung; USA; Norwegen